Results from a large multinational clinical trial (guardian™1) using prophylactic treatment with turoctocog alfa in adolescent and adult patients with severe haemophilia A: safety and efficacy. (7th May 2013) - Lentz, S. R.; Misgav, M.; Ozelo, M.; Šalek, S. Z.; Veljkovic, D.; Recht, M.; Cerqueira, M.; Tiede, A.; Brand, B.; Mancuso, M. E.; Seremetis, S.; Lindblom, A.; et al.
Summary: Recombinant factor VIII (rFVIII) products provide a safe and efficacious replacement therapy for prophylaxis and treatment of bleeding episodes in patients with severe haemophilia A. This multinational, open‐label, non‐controlled trial investigated the safety and efficacy of turoctocog alfa, a new rFVIII product. The primary objective was to evaluate safety. A total of 150 patients (24 adolescents and 126 adults) with severe haemophilia A (FVIII activity ≤1%), with at least 150 exposure days (EDs) to any FVIII product and no history of inhibitors were enrolled, and 146 patients (97%) completed the trial. All patients received prophylaxis with turoctocog alfa for approximately 6 months and had a mean of 85 EDs during the trial. None of the patients developed FVIII inhibitors, there were no indications of early FVIII inhibitor development and no safety concerns were identified. A total of 225 adverse events were reported in 100 (67%) patients, with the most common being events associated with dosing procedures, headaches, and nasopharyngitis. A total of 499 bleeding episodes were reported during the trial, the majority (89%) were controlled with 1–2 infusions of turoctocog alfa. Based on patient reports, the success rate (defined as 'excellent' or 'good' haemostatic response) for treatment of bleeding episodes was 81%. The overall median annualized bleeding rate was 3.7 (interquartile range: 8.7) bleeds/patient/year. In conclusion, turoctocog alfa provides a new, safe and effective alternative for prophylaxis and treatment of bleeding episodes in patients with haemophilia A.